PLoS Computational Biology Issue Image | Vol. 17(12) December 2021 (PLOS Computational Biology, 2022)
Neuronal dynamics driven by thalamo-cortical interactions and revealed by time-frequency analysisThe mechanism underlying the emergence of a stable alpha band(8-12Hz) oscillation during general anesthesia is still unclear but could result from the network interactions between various brain regions. These regions can generate membrane transition patterns between Up and Dow states. Zonca and Holcman examined the influence of synaptic short-term plasticity on the development of stable oscillations between excitatory and inhibitory neurons using neuronal network models. They report that the alpha-band, emerges spontaneously after excitatory stimuli are shut off. However, fragmentation of the alpha band may result from transitions from Up to Down state or from reducing the synaptic random activity. Twitter: @LouZonca, @David_Holcman, @HolcmanLabImage Credit: Lou Zonca and David Holcman, PSL Research University